ANALISIS PERHITUNGAN, PENCATATAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 23 ATAS PENGADAAN BARANG DALAM HAL INI JASA PENYEWAAN BARANG BERAT PADA PT.WILLIAM MAKMUR PERKASA - Tinangon, Cicilia; Saerang, David Paul Elia; Elim, Inggriani (Universitas Sam Ratulangi, 2015)
In running the government, a State must run the economy well. This affects the country for the prosperity of society development in order to achieve the objectives set by the State Act. One aspect in the implementation of the necessary development funding comes from tax revenue. The purpose of this study was to determine the mechanism of calculation, recording and reporting of Income Tax Article 23 on the procurement of goods in this respect rental services heavy loads PT.William Perkasa Makmur. The analysis method used in this research is descriptive analysis method. The results showed that as a company engaged in the field of contracting and rental of heavy equipment, PT. William Makmur Perkasa continue to provide tools that have the best quality and the weight to be able to sustain the work. The company realizes the development in this area both by the Government and private parties, seen also with the advent of the projects undertaken by the Government to prepare the facilities and infrastructure to support the development of the area, of course, which is a prerequisite for the entry of investors in investing. Laws and regulations on taxation applicable always changes the company should remain always pay attention to it. This is important so that it can determine the amount of income tax 23 in accordance with the existing rules.